Époques au futur. Usages de la périodisation historienne dans la littérature d’anticipation - Pierre-Antoine Marti (Tracés, 2019)
Futuristic fiction relies strongly on the concept of the “epoch” when authors in the genre imagine a hypothetical future. This concept has been theorised, developed and applied by historians throughout modern times. By analysing these fictional epochs, the names given to them and how they are constructed, this article studies how SF writers have envisaged the future of mankind and explores the characteristic conceptions of history they developed (progressive, regressive, cyclical, etc.). It is based on a selection of American and British science-fiction novels and historiographical theories. Its aim is to explore the nature of this non-historian use of the concept of epoch, which involves specific ways of interpreting and writing history.